2019
DOI: 10.1093/europace/euz296
|View full text |Cite
|
Sign up to set email alerts
|

Early improvement of left ventricular ejection fraction by cardiac resynchronization through His bundle pacing in patients with heart failure

Abstract: Aims Permanent His bundle pacing (p-HBP) can correct intraventricular conduction disorders and could be an alternative to traditional cardiac resynchronization therapy (CRT) via the coronary sinus. We describe the short-term impact of HBP on left ventricular ejection fraction (LVEF) and improvement of left intraventricular synchrony. Methods and results This prospective descriptive study, performed from January 2018 to Februa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
0
19
0
2
Order By: Relevance
“…The implantation of His bundle lead has been explained thoroughly elsewhere89; briefly, the SelectSecure MRI‐SureScan 3830 lead (Medtronic, Minneapolis, MN, USA) was advanced through a Medtronic C315 His catheter introducer with the distal electrode/screw located just at the tip of the catheter. We mapped the septum, and then we paced and checked the His bundle capture: either selective (capture of only the His bundle with or without correction of the LBBB) or nonselective 12 (capture of the His bundle and adjacent myocardium, with or without correction of the LBBB).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The implantation of His bundle lead has been explained thoroughly elsewhere89; briefly, the SelectSecure MRI‐SureScan 3830 lead (Medtronic, Minneapolis, MN, USA) was advanced through a Medtronic C315 His catheter introducer with the distal electrode/screw located just at the tip of the catheter. We mapped the septum, and then we paced and checked the His bundle capture: either selective (capture of only the His bundle with or without correction of the LBBB) or nonselective 12 (capture of the His bundle and adjacent myocardium, with or without correction of the LBBB).…”
Section: Methodsmentioning
confidence: 99%
“…These benefits of HBP were reported for the first time by Narula and El‐Sherif et al, 3,4 and they are physiopathologically supported by the theory of the longitudinal dissociation in the His Bundle. Therefore, in patients with an indication for cardiac resynchronization therapy (CRT), p‐HBP could be an alternative to or even replace classic CRT via the coronary sinus, 5‐9 as it achieves physiological biventricular activation through the native conduction system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, a few studies indicated that HBP may be equal or superior to conventional biventricular pacing (BVP) with regard to acute hemodynamic improvement, reverse remodeling and clinical outcome. [43][44][45] In 2020, LBBAP was only 3 years old but attracted already considerable interest. For LBBAP, the 3830 lead is introduced transvenously and subsequently screwed through the interventricular septum until the tip of the lead is (almost) at the većao se s 5 u 2014. na 75 u 2018. godini.…”
Section: Resynchronization Therapy Including His Bundle Septal Andmentioning
confidence: 99%
“…Tijekom 2020. godine nekoliko je istraživanja pokazalo da bi HBP mogao biti jednako dobar ili superiorniji od konvencionalne biventrikularne elektrostimulacije (BVP) s obzirom na akutno hemodinamsko poboljšanje, reverzno remodeliranje i klinički ishod. [43][44][45] Godine 2020. LBBAP je imao samo 3 godine, ali je već privukao znatan interes.…”
Section: Resynchronization Therapy Including His Bundle Septal Andunclassified